Methodological bases of forecasting and planning in the field of development of strategic decisions in audit, analysis and taxation (Economics and region, 2023)
The article systematizes the components of methodological support for forecasting and planning in the field of developing strategic decisions in audit, analysis and taxation: basic concepts, as well as types, stages, levels, objects, principles, methods of planning and forecasting, models, planning and forecasting indicators. Types of forecasts, scenarios of the development of events in forecasting, approaches of scientists to distinguishing stages of forecasting, methods of forecasting and planning, principles on which planning and forecasting calculations are based, peculiarities of the organization of analytical work and planning decisions regarding the organization of audits at the level of business entities are considered , the specifics of developing a strategy for the development of audit activity entities, the specifics of forming strategic decisions in the field of taxation. When developing solutions in the field of taxation, it is suggested to use special methods of tax planning simultaneously with general methods of programming and planning (methods of direct reduction of the object of taxation, replacement and distribution of relations, delegation of taxes to a satellite enterprise, use of accounting policies, and others). The operational components of planning and forecasting of strategic decisions are studied: technical-technological, financial, social, personnel and management. Attention is focused on the fact that planning and forecasting calculations in the field of development of strategic decisions in audit, analysis and taxation should be based on the principles of complexity, systematicity, continuity, scientific validity, practical orientation, variability, coherence, as well as on the expediency of taking into account relationships between economic indicators reflected in accounting and reporting forms. It has been proven that the implementation of the methodological toolkit in the practical plane will ensure the assessment of the state of the accounting and analytical system, as well as the identification of characteristic trends, problematic aspects, influencing factors, the formation of strategic goals, the development of plans and forecast options for solutions, their substantiation, the selection of the optimal strategic solution and the development of tactical measures for the further implementation of such a decision.
Keywords: forecasting; planning; methodological foundations; decision making; strategic decisions; audit; analysis; taxation